Transcript Analysis of Zebrafish GLUT3 Genes, slc2a3a and slc2a3b, Define Overlapping as Well as Distinct Expression Domains in the Zebrafish (Danio rerio) Central Nervous System - Lechermeier, Carina G.; Zimmer, Frederic; Lüffe, Teresa M.; Lesch, Klaus-Peter; Romanos, Marcel; Lillesaar, Christina; Drepper, Carsten (Frontiers in Molecular Neuroscience, 2019)
The transport of glucose across the cell plasma membrane is vital to most mammalian cells. The GLUT (also called SLC2A) family of transmembrane solute carriers is responsible for this function in vivo. GLUT proteins encompass 14 different isoforms in humans with different cell type-specific expression patterns and activities. Central to glucose utilization and delivery in the brain is the neuronally expressed GLUT3. Recent research has shown an involvement of GLUT3 genetic variation or altered expression in several different brain disorders, including Huntington’s and Alzheimer’s diseases. Furthermore, GLUT3 was identified as a potential risk gene for multiple psychiatric disorders. To study the role of GLUT3 in brain function and disease a more detailed knowledge of its expression in model organisms is needed. Zebrafish (Danio rerio) has in recent years gained popularity as a model organism for brain research and is now well-established for modeling psychiatric disorders. Here, we have analyzed the sequence of GLUT3 orthologues and identified two paralogues in the zebrafish, slc2a3a and slc2a3b. Interestingly, the Glut3b protein sequence contains a unique stretch of amino acids, which may be important for functional regulation. The slc2a3a transcript is detectable in the central nervous system including distinct cellular populations in telencephalon, diencephalon, mesencephalon and rhombencephalon at embryonic and larval stages. Conversely, the slc2a3b transcript shows a rather diffuse expression pattern at different embryonic stages and brain regions. Expression of slc2a3a is maintained in the adult brain and is found in the telencephalon, diencephalon, mesencephalon, cerebellum and medulla oblongata. The slc2a3b transcripts are present in overlapping as well as distinct regions compared to slc2a3a. Double in situ hybridizations were used to demonstrate that slc2a3a is expressed by some GABAergic neurons at embryonic stages. This detailed description of zebrafish slc2a3a and slc2a3b expression at developmental and adult stages paves the way for further investigations of normal GLUT3 function and its role in brain disorders.